The Scientific Advances in Psychoactives Versus Artifacts in Amphetamine Analysis - Ricardo Jorge Dinis-Oliveira (Psychoactives, 2025)
Psychoactive substances, including illicit drugs, prescription medications, and novel psychoactive compounds, are frequently analyzed in biological and in non-biological samples. Interpreting results is paramount for ensuring proper medical treatments and judicial decisions. However, false-positive results—where a sample is incorrectly identified as containing a psychoactive substance—remain a persistent issue. In other words, it is important to invest in understanding the meaning of toxicological results. Cross-reactivity in immunoassays, sample contamination, analytical interference with certain endogenous and exogenous substances, inadvertent and accidental exposure due to environmental contamination, second-hand smoke inhalation, or unintentional dermal or mucosal contact with drug residues are some of the major issues to consider. This perspective highlights major sources of artifacts in interpreting amphetamine analytical results in order to provide proper toxicological interpretations.